2018
DOI: 10.15835/nbha47111367
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antifungal Activity of a New Bioproduct Obtained from Grape Seed Proanthocyanidins on Botrytis cinerea Mycelium and Spores

Abstract: Botrytis cinerea is a necrotrophic fungus that affects over 200 plant species. In vineyards, this pathogen is responsible for one of the most important diseases, commonly known as botrytis bunch rot or grey mould. Keeping infection under control with synthetic fungicides leads to an increased biological resistance of pathogen populations. An alternative way to synthetic products is to obtain natural fungicides by using bioactive compounds of plants. This study focuses on the antifungal properties of a new biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These phenolic acids probably caused damages to the mycelial structure of F. oxysporum, as previously mentioned, and reduced its growth. Other studies have highlighted that phytopathogen inhibition mechanisms vary depending on phenolic compounds and the fungi tested (Nechita et al, 2019;Joaquín-Ramos et al, 2020). In this study, a different trend was observed for Alternaria spp.…”
Section: Antifungal Activity Of Hydrolysatesmentioning
confidence: 53%
See 1 more Smart Citation
“…These phenolic acids probably caused damages to the mycelial structure of F. oxysporum, as previously mentioned, and reduced its growth. Other studies have highlighted that phytopathogen inhibition mechanisms vary depending on phenolic compounds and the fungi tested (Nechita et al, 2019;Joaquín-Ramos et al, 2020). In this study, a different trend was observed for Alternaria spp.…”
Section: Antifungal Activity Of Hydrolysatesmentioning
confidence: 53%
“…In addition, damages to the mycelial structure of F. oxysporum exposed to hydrolysates of RGM seeds, PGM seeds and WGM seeds were observed using microscopic examinations (Figure 2). According to previous reports, phenolic compounds including simple molecules (phenolic acids) and complex structures (flavanols, flavonols and anthocyanins) have been reported to be directly involved in the defence mechanisms of plants against pathogenic fungi (Ahmed et al, 2017;Nechita et al, 2019). In addition, Luo et al (2016) confirmed that phenolic compounds could increase the cell permeability, thus reducing fungal growth.…”
Section: Antifungal Activity Of Hydrolysatesmentioning
confidence: 83%
“…In accordance with our findings, a previous study showed that the ethanolic extract of grapefruit tendrils had a significant fungicidal effect against different Fusarium species such as F. oxysporum , F. culmorum , F. solani , F. coeruleum , F. sporotrichioides , F. verticillioides , and F. tabacinum, while another species, Rhizoctonia solani, showed significant resistance [ 44 ]. Another study showed that polymeric proanthocyanidins isolated from grape seeds by ethanolic extraction had significant antifungal activity against Botrytis cinerea by inhibiting the spore germination [ 45 ]. Another study showed that the lonely application of GSE did not induce any inhibition of the mycelial growth of A. alternata [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The polyphenol content in G. max and M. sativa significantly increased following AMF inoculation. This class of New Phytologist chemicals has been widely reported to be protective against necrotrophic pathogens (Haile et al, 2017;Nechita et al, 2019). For example, a polyphenol bioproduct inhibited spore germination and mycelial growth in the necrotrophic pathogen Botrytis cinerea (Nechita et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This class of chemicals has been widely reported to be protective against necrotrophic pathogens (Haile et al ., 2017; Nechita et al ., 2019). For example, a polyphenol bioproduct inhibited spore germination and mycelial growth in the necrotrophic pathogen Botrytis cinerea (Nechita et al ., 2019). Additionally, increases in foliar N (as observed in our study) could increase tolerance to necrotrophs such as Alternaria and Fusarium , because plants suffering from nitrogen limitation have a lower photosynthetic rate and slower growth, increasing their susceptibility (Snoeijers et al ., 2000; Fagard et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%